Applicability evaluation of the diagnostic ratios consisting of bicyclic sesquiterpanes to source identification for seriously weathered spilled oils. Issue 47 (18th November 2019) - Han, Bin; Zheng, Li; Yu, Shun
Abstract : Marine oil spills often cause long-term harm to the polluted environment. Abstract : Marine oil spills often cause long-term harm to the polluted environment. The absence of many important components makes it more difficult to identify the source of an oil spill. Traceability identification of seriously weathered oil spill has always been a difficult task due to the influence of the complicated weathering process. Therefore, it is particularly important to screen and verify the new indexes to solve the problem of identification of severe weathering oil spill. As a kind of common biomarker, the bicyclic sesquiterpanes represent a research hotspot in the field of identification of oil spills. The stability and applicability of bicyclic sesquiterpanes in oil spills in different time points have been assessed by comparing laboratory simulation weathering experiment and beach weathering experiment samples. By using the commonly used oil spill identification method including the t -test, similarity method and repeatability limit method, 12 new diagnostic ratios (DRs) of bicyclic sesquiterpanes were screened and appraised. These diagnostic ratios are applicable to the identification of unweathered crude oil samples obtained from different regions. In both severe weathering processes, only the ratio of total pentamethyldecahydronaphthalene to total pentamethyldecahydronaphthalene and hexamethyldecahydronaphthalene remained relatively stable. This has a good potential for the identification of the source of severe weathering oil spills. If it has been verified by a variety of oil products, it can be recommended as the identification index of severe weathering oil spills.